Experimental modeling of the unburial behaviour of pipelines - Byrne, B; Schupp, J; Martin, C; Oliphant, J; Maconochie, A; Cathie, D (2008)
Submarine pipelines are used to transport hot crude oil or gas from satellite production fields to a central offshore production platform. These pipelines are commonly laid in trenches that are subsequently backfilled, so that they are protected from damage and to gain additional thermal insulation from the surrounding soil. A discussion covers the interaction of a buried pipeline and the surrounding soil during various unburial processes; upheaval buckling; pipeline floatation; failure mechanisms at different depths; correlation of the drained response with mechanisms of failure; and liquefaction along the pipe. This is an abstract of a paper presented at the 2008 Offshore Technology Conference (Houston, TX 5/5-8/2008).